A multiple intervention strategy for reducing femoral neck stress injuries and other serious overuse injuries in U.S. Army Basic Combat Training. - Scott SJ; Feltwell DN; Knapik JJ; Barkley CB; Hauret KG; Bullock SH; Evans RK; Scott, Shawn J; Feltwell, David N; Knapik, Joseph J; Barkley, Colleen B; Hauret, Keith G; et al. (Military Medicine, 2012)
We hypothesized that the use of evidence based injury prevention strategies would lead to a reduction in the incidence of femoral neck stress injuries (FNSIs) and other serious overuse injuries in U.S. Army Basic Combat Training (BCT). An injury prevention strategy began in late 2008 that included: (1) leadership education, (2) leadership enforcement of proven methods, and (3) injury surveillance and reporting. Data on FNSI and removal from training for injury were analyzed based on the fiscal year 2006 through 2010 (n = 210,002). For men, FNSI were reduced from 13 to 20 cases/10,000 recruits per year (2006-2008) to 8 cases/10,000 recruits in 2010 (p < 0.01); for women, FNSI were reduced from 35 to 41 cases/10,000 recruits per year (2006-2008) to 18 cases/10,000 recruits per year in 2010 (p < 0.01). For men, removals from training for injury were reduced from 0.8 to 1.1 cases/100 recruits per year (2006-2008) to 0.5 cases/100 recruits in 2010 (p < 0.01); for women removal from training for injury was reduced from 2.3 to 2.4 cases/100 recruits (2006-2008) to 1.0 case/100 recruits per years in 2010 (p < 0.01). The time course of the changes suggests that following specific injury prevention methods was effective in reducing injuries.